All-fiber, wavelength-tunable ultrafast praseodymium fiber laser - Ahmad, Harith (Chinese Laser Press, 2018)
The interest in tunable ultrafast fiber lasers operating in the 1.3 μm region has seen a significant increase due to rising demands for bandwidth as well as the zero-dispersion characteristic of silica fibers in this wavelength region. In this work, a tunable mode-locked praseodymium-doped fluoride fiber (PDFF) laser using single-walled carbon nanotubes as a saturable absorber is demonstrated. The mode-locked pulses are generated at a central wavelength of 1302 nm with a pulse repetition rate of 5.92 MHz and pulse width of 1.13 ps. The tunability of the mode-locked PDFF laser covers a tuning range of 11 nm.